THE CURRENT TRADE SITUATION AND DETERMINANTS OF SINO-AUSTRALIA INTRAINDUSTRY TRADE - Lijun Jia; Maoguo Wu (European Scientific Journal, ESJ, 2014)
Economic globalization has promoted the world market to an everexpanding one. It has also achieved regional unity. In this case, the frequent trade between China and Australia has been intensified with increasing frequency. Therefore, the Sino-Australia intra-industry trade has started to develop. In this paper, we measure the index of IIT, HIIT and VIIT of Sino- Australia intra-industry trade and argue that the condition of Sino-Australia intra-industry trade remains low while the condition of intra-industry trade of finished goods is higher than that of primary commodity. Based on the analysis, we then develop a model to capture the main determinants of HIIT and VIIT in every industry. Policy suggestions are put forward accordingly to promote further development on Sino-Australia intra-industry trade.